Comprehensive evolutionary analysis of growth-regulating factor gene family revealing the potential molecular basis under multiple hormonal stress in Gramineae crops - Wang, Wei; Cheng, Mingxing; Wei, Xiao; Wang, Ruihua; Fan, Fengfeng; Wang, Zhikai; Tian, Zhihong; Li, Shaoqing; Yuan, Huanran (Frontiers in Plant Science, 2023)
Growth-regulating factors (GRFs) are plant-specific transcription factors that contain two highly conserved QLQ and WRC domains, which control a range of biological functions, including leaf growth, floral organ development, and phytohormone signaling. However, knowledge of the evolutionary patterns and driving forces of GRFs in Gramineae crops is limited and poorly characterized. In this study, a total of 96 GRFs were identified from eight crops of Brachypodium distachyon, Hordeum vulgare, Oryza sativa L. ssp. indica, Oryza rufipogon, Oryza sativa L. ssp. japonica, Setaria italic, Sorghum bicolor and Zea mays. Based on their protein sequences, the GRFs were classified into three groups. Evolutionary analysis indicated that the whole-genome or segmental duplication plays an essential role in the GRFs expansion, and the GRFs were negatively selected during the evolution of Gramineae crops. The GRFs protein function as transcriptional activators with distinctive structural motifs in different groups. In addition, the expression of GRFs was induced under multiple hormonal stress, including IAA, BR, GA3, 6BA, ABA, and MeJ treatments. Specifically, OjGRF11 was significantly induced by IAA at 6 h after phytohormone treatment. Transgenic experiments showed that roots overexpressing OjGRF11 were more sensitive to IAA and affect root elongation. This study will broaden our insights into the origin and evolution of the GRF family in Gramineae crops and will facilitate further research on GRF function.